Head, chest and abdominal circumferences for predicting gestational age in newborn infants - Nengah Supatra, Nengah Supatra (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 1992)
The purpose of this study is to examine head, chest dan abdominal circumferences as measurements for predicting gestational age of the newborn infant.During the period of August 1989 to December 1990, 1033 newborns with known gestational age were studied. Anthropometric measurements were done in the first two hours after birth, using measuring tapes by two examiners.High correlations were found between head, chest and abdominal circumferences with gestational age, and the linear aquations were Y= 0,075 X + 14,310 (Coefficient of Correlation/r = 0,72); Y= 0,066 X + 18,33 (r = 0,71) and Y= 0,056 X + 22,34 (r = 0,67) respectively. Further analysis by multiple regression revealed that gestational age (in weeks) as function of head, chest and abdominal circumferences (in millimeter) was Y= 0,036 X1 + 0,023 X2 + 0,020 X3 + 13,699.Measurements of head, chest and abdominal circumferences in the first two hours after birth can be used for estimating gestational age in the newborn infant.Key Words: head circumference - trunk circumference - abdominal circumference - gestational age - newborns